Percutaneous Coronary Intervention in Post-Infarction Ventricular Septal Rupture - Suryono Suryono; Naesilla Naesilla; Ika Aulia Kurniasari; Toyibatul Hidayati; Madha Qoyyulledy Tursina; Farid Lutfi Madhoni; Mirah Susanti Kartika Sari (Health Notions, 2021)
Background: Ventricular septal rupture (VSR) is a fatal mechanical complication following acute myocardial infarction (AMI). The definitive treatment remains surgical repair, however several aspects are still debatable, including the timing of surgery. Patient’s refusal of treatment and lack of medical facilities put other challenges in management of VSR. Case presentation: A-48-year-old male with a history of diabetes mellitus and hypertension came with a late-presentation anterior AMI, and refused the reperfusion therapy. By the third day, he developed VSR and cardiogenic shock. The patient was also against any referral plan for further therapy. Hemodynamic status was optimally controlled with vasopressor and inotropic agents. The patient was discharged with a grade II-III New York Heart Association (NYHA) on the tenth day. In follow up evaluation a week later, the patient presented limb swelling and functional NYHA class III-IV. The patient agreed to received percutaneous coronary intervention (PCI). Drug eluting stent (DES) in left anterior descending (LAD) coronary artery was implanted successfully without defect closure. Follow-up after 12-months revealed no signs or symptoms of decompensated heart failure. Keywords: ventricular septal rupture; percutaneous coronary intervention; acute myocardial infarction